Phytochemical Studies of Ficus deltoidea var kunstleri - Md Jamal, Nor Afifah; Ahmad, Kartini; Nafiah, Mohd Azlan (Asian Journal of Chemistry, 2017)
Ficus deltoidea or locally known as Mas Cotek is one of the traditional medicinal plants. The aim of this work is to determine the chemical structure of isolated compounds from F. deltoidea var. kunstleri by using various spectroscopy and also by comparison with previous literature data. Chromatographic purification of hexane and dichloromethane crude extract of F. deltoidea var. kunstleri (leaves and stem barks) yielded four pure compounds viz., a-amyrin (1), lupeol (2) bergapten (3) and b-amyrin cinnamate (4) along with four mixtures; mixture of sesquiterpenes: tanacetene (5) and b-elemene (6), mixture of sterols; stigmasterol (7) and b-sitosterol (8), a mixture of triterpenes: lupeol, a,b-amyrin (9), lupenone, a,b-amyrenone (10). These compounds were identified through analysis mainly 1D and 2D NMR and also by comparison with previous studies. Even though 1, 3, 4, 5, 6, 7 and 10 are known compounds, but our best of knowledge these compounds are first time reported from this species.